The Effect of Financial Distress and Transfer Pricing on Tax Avoidance: The Moderating Role of Gender Diversity in Indonesian Mining Companies - Emelda Anggraini; Sekar Mayangsari; Nurhastuty Kesumo Wardhani (PT. Cendekia Sapta Indonesia, 2026)
Purpose ― This study aims to examine the effect of financial distress and transfer pricing on tax avoidance, as well as the moderating role of female directors, using panel data from mining companies listed on the Indonesia Stock Exchange Methods ― This study analyzes panel data of mining companies listed on the Indonesia Stock Exchange from 2020 to 2024 with 22 companies and 110 data observations. Purposive sampling and panel data regression using EViews are applied to test the research hypotheses Findings ― The results show that financial distress positively and significantly affects tax avoidance in mining companies, while transfer pricing has no significant effect. Female directors are found to weaken the impact of financial distress on tax avoidance, but they do not moderate the relationship between transfer pricing and tax avoidance. Implication ― The findings indicate that financial distress is a key driver of tax avoidance, underscoring the importance of financial risk management in constraining aggressive tax behavior. From a theoretical perspective, these results support Agency Theory, suggesting that financial pressure intensifies conflicts of interest between managers and shareholders, leading managers to engage in tax avoidance to preserve firm resources. The insignificant role of transfer pricing implies that related-party transactions are not the primary tax avoidance mechanism in the Indonesian mining sector, reflecting the effectiveness of regulatory oversight. Furthermore, the moderating role of female directors reinforces corporate governance theory and gender diversity literature, indicating that female board representation enhances monitoring quality and ethical decision-making, thereby weakening the tendency toward opportunistic tax behavior under financial distress Originality ― The originality of this study lies in analyzing the moderating role of female directors in the relationship between financial distress, transfer pricing, and tax avoidance in the mining sector, providing new evidence on the influence of board gender diversity on tax avoidance under financial pressure